Vegetarian and Vegan Private Label Products as a Challenging Trend in Addressing the Customers Within Sustainable Food Consumption—A Case Study of Slovakia - Košičiarová, Ingrida; Kádeková, Zdenka; Šedík, Peter; Smutka, Ĺuboš (Frontiers in Sustainable Food Systems, 2022)
The meat consumption at the current level is highly unsustainable. Because of the problems that meat production causes to the environment, it is considered as one of the main problems. Vegetarian and vegan private label products represent a new challenging trend in addressing the customers within sustainable food consumption at affordable prices. The submitted paper aimed to find out whether Slovak consumers know and subsequently buy products of the private brand targeted on vegans and vegetarians, in which product categories they do so, how they perceive them and what attracts and discourages them. The research was carried out in the period from September to December 2020, when a total of 2,011 respondents from all over Slovakia took part. As we have focused only on consumers who know the product line of private labels targeted on vegans and vegetarians (product line of vegan and vegetarian products), we have further analyzed and interpreted only the answers of 978 respondents. For the need to obtain the main aim of the research, we have formulated four theoretical assumptions and five hypotheses, whose veracity was verified with the use of selected statistical methods and techniques processed out at statistical programs XL Stat, SAS Enterprise Guide 7.1. and SAS 9.4. The key finding of our research is, that even if it could be assumed that the products of this specific private label will be bought only by respondents from the vegan or vegetarian category, the opposite is true—the private label is known and bought by the respondents from the category “I eat everything,” which means that it is necessary to think about this product line, to wider it and continue in the improvement of its quality as this is what the customers want.